Excursion guide for field trip V3 : ‘Islands of Fayal and Pico’ - Machado, Frederico (1982)
The Azores are situated at the intersection of the mid-Atlantic ridge with the Azores-Gibraltar fracture belt which is part of the Alpine orogenic chain. At this triple junction converge the so called American, Eurasian, and African plates. On 6 of the islands there are 9 active volcanoes: the number of independent submarine vents is unknown, but 4 had recorded eruptions since the 15th century. Seismicity of the islands is considerable, which certainly results from plate movement. According to one of the tectonic proposed for the area, the mid-Atlantic rift could cross all the islands with active volcanoes (Fayal, Pico, San Jorge, Graciosa, Terceira and San Miguel). Expansion along the rift would be accompanied by shear at the associated transform faults, this shear being responsible for most of the frequent earthquake swarms. The present tectonic situation is further complicated by the effect of the Alpine movements, which also seem to produce crustal expansion to the west of a no-strain point at longitude 22˚ West. Another tectonic model assumes simply that the mid-Atlantic rift is situated between Fayal and Flores, and is intersected by a minor rift and spreading centre (the Terceira rift) that merges into the Azores-Gibraltar fracture zone.